A qualitative choice analysis: examining the factors shaping the patterns of mortgage payment irregularities - Kabir, Mohammad Hasan (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Master of Science in Applied Economics, 2023.